Sonic boom mitigation via shape optimization using an adjoint method and application to a supersonic fighter aircraft - Maute, Kurt; Farhat, Charbel; Argrow, Brian; Nikbay, Melike (European Journal of Computational Mechanics, 2008)
This paper describes a computational method for the analysis and mitigation via shape optimization of the sonic boom associated with supersonic flight. The method combines a CFD approach for determining the near-field pressure field and an acoustic scheme for predicting the initial shock pressure rise at the ground. Two venues are considered for computing the ground signature. The performance of both approaches is evaluated using flight test data of two different configurations of an F5 fighter aircraft.